Test–re-test reliability and inter-rater reliability of a digital pelvic inclinometer in young, healthy males and females - Beardsley, Chris; Egerton, Tim; Skinner, Brendon (PeerJ, 2016)
Objective. The purpose of this study was to investigate the reliability of a digital pelvic inclinometer (DPI) for measuring sagittal plane pelvic tilt in 18 young, healthy males and females. Method. The inter-rater reliability and test–re-test reliabilities of the DPI for measuring pelvic tilt in standing on both the right and left sides of the pelvis were measured by two raters carrying out two rating sessions of the same subjects, three weeks apart. Results. For measuring pelvic tilt, inter-rater reliability was designated as good on both sides (ICC = 0.81–0.88), test–re-test reliability within a single rating session was designated as good on both sides (ICC = 0.88–0.95), and test–re-test reliability between two rating sessions was designated as moderate on the left side (ICC = 0.65) and good on the right side (ICC = 0.85). Conclusion. Inter-rater reliability and test–re-test reliability within a single rating session of the DPI in measuring pelvic tilt were both good, while test–re-test reliability between rating sessions was moderate-to-good. Caution is required regarding the interpretation of the test–re-test reliability within a single rating session, as the raters were not blinded. Further research is required to establish validity.
Keywords: Reliability; Pelvic tilt